Evaluating Multimodal Transportation Education In Indonesia - Larsen Barasa; Retno Sawitri Wulandari; Jaya Alamsyah; April Gunawan Malau; Marudut Bernadtua Simanjuntak (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research investigates the effectiveness of transportation education programmes in Indonesia, focusing on multimodal transportation. Through qualitative analysis of 50 Indonesian cadets enrolled in transportation programmes, the study assesses knowledge retention and application. Findings reveal strengths in curriculum breadth and practical application, but challenges in knowledge retention, faculty competence, and industry relevance. Recommendations include curriculum enhancements, active learning strategies, faculty development, industry collaboration, technology integration, and a global perspective. By addressing these recommendations, Indonesia can enhance the quality and relevance of transportation education, better preparing cadets for the complexities of the transportation industry.